Implementasi Metode Linear Discriminant Analysis (LDA) Untuk Klasifikasi Pengambilan Mata Kuliah Pilihan - Ayu Anggrestianingsih; Agus Wahyu Widodo; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Faculty of Computer Science is one of the best faculties at Brawijaya University. The Faculty of Computer Science (FILKOM) has several majors, one of which is the Informatics major which is most in demand by FILKOM students. When students enter semester 5, they are required to choose interests that are in accordance with their abilities. There are a variety of fields of study offered, one of which is artificial intelligence, which in this study, will focus on taking electives of interest in the field of Artificial Intelligence, to help students choose interests in accordance with their abilities. In this study, using the Linear Discriminant Analysis (LDA) method in order to get good accuracy for taking courses. The training data used as many as 30 data, where each class consists of 15 data for yes classes and 15 data for classes not with 5 elective courses. Then obtained accuracy values ​​for each elective course such as 40% Fuzzy Logic, 40% Decision Support System, 80% Digital Image Processing, 20% Evolution Algorithm and 40% Expert System